The agricultural geography of Møn: A survey and examples - Kamp, Aa. H. (ERDKUNDE, 1962)
The island of Mön owes its present shape essentially to the Vistula (Würm) glaciation, which also here gave rise to a flat, dome-shaped ground moraine relief. This is divided into two parts by the Borre Marsh, a depression formerly occupied by the Litorina Sea, and today by bogs and meadows. The base of the island is the soft limestone, but the soils derive almost exclusively from glacial deposits, which explains the immediate proximity of the poorest and richest soils. The inhabitants have lived mainly in closed villages since the Iron Age, but these were still separated from each other by extensive swamps, bogs and heaths until deep into the 18th century. During this period, however, a distinct cultural landscape metamorphosis occurred, when the enclosure movement brought the previous wasteland under the plow and dissolved the rural village settlement in favor of a scattered settlement spread over the whole district. On Mön, this movement began around 1765 and lasted until 1822. Typical examples are traced from their beginnings to the present. In order to counteract the rural exodus that emerged towards the end of the 19th century, the state purchased numerous parcels of land from 1900 onwards, on which it settled agricultural workers as Katner. However, when these measures met with little success and the rural exodus continued, in 1919 the government ordered the subdivision of parsonages and, in some cases, estates, in order to create viable medium-sized farms. As an example, the division of a former parsonage is described here. Since then, the productivity of agriculture has taken a great upswing, strongly challenged by the development of the long existing cooperative system. The agricultural area has decreased by 1 ½ % from 1939 to 1960, but the yield performance has been considerably increased. Especially the one of the mentioned examples (Dalmosegaard) shows how the management of the original cereal production was gradually shifted to dairy farms, sugar production and seed cultivation, with increasing yields as a consequence.